Integrated process modelling for the Kalgoorlie Nickel Smelter - G Sartor; A Rich; D Grimsey; M White; R Forzatti (The Australasian Institute of Mining and Metallurgy, 2024)
An in-depth process model was developed for the pyrometallurgical, off-gas systems and water balance of the Kalgoorlie Nickel Smelter. This model was used to assess plant capacity with changing concentrate grades, increased throughput and tighter environmental emissions under a range of potential future operating conditions. Comparison of modelled results allowed for flow sheet optimisation across a range of metrics including sustainability, processing capacity and costs. Process modelling software, METSIM® (ver 2020.06 by METSIM International), was used to simulate the flash furnace, integrated electric slag cleaning furnace, Pierce-Smith converters, matte granulation, waste heat boiler, hot gas handling equipment, wet gas cleaning plant and acid plant. The METSIM® model was divided into three separate, yet interconnected models: metals, off-gas and water balancing. This allowed for improved modelling efficiency and traceability while minimising manual error. The METSIM® model was supported by inputs from other specialised software. Chemical thermodynamics software, FactSage™ (ver 8.2 by GTT Technologies), was used to establish relationships for the flash furnace fluxing strategy and determine the operating temperature. Arena® (ver 16.0 by Rockwell Automation), a discrete event modelling software, was used to simulate material movements within the aisle as well as Pierce-Smith converter operation, allowing for integration with upstream and downstream systems. A dynamic data exchange (DDE) was used to connect the results of each software package, interfacing through Excel® (version 4203 by Microsoft). The integration between models provided a streamlined approach to test capacity, bottlenecks, water consumption and emissions under a range of operating conditions, enabling a more robust process. Further downstream modelling techniques were used to assess mechanical equipment. METSIM® outputs provided key parameters for combustion assessments using computational fluid dynamics and finite element analysis for the furnace mechanical design.